A novel necroptosis-related gene signature for predict prognosis of glioma based on single-cell and bulk RNA sequencing - Guo, Kai; Duan, Xinxin; Zhao, Jiahui; Sun, Boyu; Liu, Xiaoming; Zhao, Zongmao (Frontiers in Molecular Biosciences, 2022)
Background: Glioma is the most fatal neoplasm among the primary intracranial cancers. Necroptosis, a form of programed cell death, is correlate with tumor progression and immune response. But, the role of necroptosis-related genes (NRGs) in glioma has not been well uncovered. Methods: Single-cell and bulk RNA sequencing data, obtained from publicly accessed databases, were employed to establish a necroptosis-related gene signature for predicting the prognosis of glioma patients. Multiple bioinformatic algorithms were conducted to evaluate the efficacy of the signature. The relative mRNA level of each signature genes was validated by Quantitative real-time reverse transcription PCR (qRT-PCR) in glioma cell lines compared to human astrocytes. Results: In this predict prognosis model, patients with high risk score showed a shorter overall survival, which was verified in the testing cohorts. The signature risk score was positively related with immune cell infiltration and some immune check points, such as CD276 (B7-H3), CD152 (CTLA-4), CD223 (LAG-3) and CD274 (PD-L1). Single-cell RNA sequencing analysis confirmed that glioma microenvironment consists various immune cells with different markers. The 8 NRGs of the signature were detected expressed in several immune cells. QRT-PCR results verified that all the 8 signature genes were differentially expressed between human astrocytes and glioma cells.Conclusions:The 8 NRGs correlate with immune microenvironment of glioma according to our bioinformatic analysis. This necroptosis-related gene signature may evaluate the precise of predicting prognosis of glioma and provide a novel thought in glioma investigation.